An investigation exploring gender inequality within the mining industry : a case of coal mining in Emalahleni, Mpumalanga Province of South Africa - Naidoo, Dhee (University of Pretoria, 2025)
Thesis (MSocSci (Development Studies))--University of Pretoria, 2025.